Disaster Preparedness in Elementary Schools: An Analysis of the Level of Knowledge and Preparedness of Students towards Flood Disaster - Diansasnita, Aisha; Hutami, Citra Kirana; Rahma, Fidela; Nazia, Safira Intan; Harianto, Maria Kireina; Shahnaz, Yunisa Dinda Aulia (Tarqabin Nusantara Group, 2025)
Indonesia is one of the 4,444 disaster-prone countries, both in terms of natural and man-made disasters. Indonesia is one of the countries prone to flooding because it has high rainfall. Flood is a natural disaster where drainage cannot accommodate excessive water that occurs in an area so that it can cause inundation that is detrimental to the area. Floods can occur in all regions including Malang Regency. The Regional Disaster Management Agency (BPBD) of Malang Province recorded 71 natural disasters in 2018, most of which were floods and landslides. Disaster drills or preparedness are fundamental training to build a safe and strong culture, especially for children. Disaster preparedness measures can be taken early on through socialization conducted at SDN 4 Tumpang, Malang Regency. The purpose of this research is that the students are expected to understand how the steps of disaster preparedness including flood disaster. The type of research used in this study is experimental with pre-experimental research methods. This data comes from primary data obtained from pre-test and post-test scores. The population in this study were some students of SDN 4 Tumpang from class 3 as many as 7 people and class 4 as many as 10 people, with a total population of 17 respondents. The results of this study were obtained data that the average value of student knowledge before being given education was 53.74 and after being given education increased to 66.35. It shows that there is an increase in knowledge after being given education.